Dampak Tradisi Ben Ghiben Terhadap Minat Menikah Pada Masyarakat Dusun Pasar Desa Lombok Kulon Kabupaten Bondowoso - M. Salman Fikri Ramadhan; Syarafuddin, Muhsan (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2025)
The Ben Ghiben tradition is a deeply rooted marriage custom in Madurese society, particularly in Dusun Pasar, Lombok Kulon Village, Bondowoso Regency. This tradition involves the prospective groom bringing household items to the bride’s home, reflecting a matrilocal system in which the couple resides at the bride's house. This study aims to examine how the community perceives this tradition, its positive and negative impacts, and its legal standing in Islamic law. The study also focuses on the tradition’s influence on marriage interest among the younger generation, finding that Ben Ghiben is not the main factor driving marriage interest, with mental and financial readiness being more significant. This qualitative research uses in-depth interviews with several sources to understand community perceptions of this tradition. The findings indicate that Ben Ghiben provides positive effects, such as preserving local customs and easing economic burdens, but it can also pose additional financial challenges. From an Islamic law perspective, the tradition is permissible as long as it does not contradict religious principles. This study suggests that the tradition should be preserved, with material requirements adapted through mutual agreements to alleviate the financial burden on the prospective groom.